Analysis of a Laboratory Scale Thermal Energy Accumulator Using Two-Phases Heterogeneous Paraffin Wax-Water Mixtures - Reyes-Salinas, A; Henriquez-Vargas, L; Vasquez-Fajardo, J; Pailahueque-Barahona, N (Elsevier Ltd, 2020)
To reduce the cost of materials in a thermal energy accumulator, the use of water as a substitute for a mass fraction of paraffin wax was considered in the present study which evaluates the thermal behavior of a combined sensible and latent heat storage system that used a beverage can containing paraffin wax and water in different proportions for experiences of thermal energy accumulation and discharge. Unlike other applications that consider the forming of emulsions, there will be two phases within the containers. In a second stage, energy discharge experiences were realized within a 12 cans laboratory scale energy accumulator to analyze its thermal behavior. Replacing 25% of paraffin wax decreases the accumulated energy by only 12%, retaining similar energy discharge times relative to a 100% paraffin wax configuration. Shorter energy loading times and higher heat removal were observed for configurations with a higher water content. No major differences in energy discharge efficiency were found for the same wax/water content, using air velocities of 1.3 m/s and 2.6 m/s. However, in the first 60 min differences up to 25% in the heat removal were observed. Heat transfer coefficients between 18.0 W/m2K and 26.8 W/m2K were determined experimentally. © 2019 Elsevier Ltd